Reflecting on Creating a Culture of Academic Integrity at the University of Manitoba: CSAI 2023 Greetings (Canadian Perspectives on Academic Integrity, 2023)
This month, we publish our first issue of the sixth volume of the Canadian Perspectives on Academic Integrity (CPAI), and highlight the abstracts from the Canadian Symposium on Academic Integrity (CSAI) 2023 hosted by The Centre for the Advancement of Teaching and Learning, University of Manitoba. This issue also features an original research article focusing on the understanding and perspectives of plagiarism of undergraduate students at the University of Toronto.